INTEGRATION OF HEALTH MONITORING SYSTEMS IN SMART HOME ENVIRONMENTS - Mohanraj Varatharaj (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The integration of health monitoring systems within smart home environments represents a transformative advancement in healthcare technology, driven by the increasing adoption of Internet of Things and rising demand for personalized healthcare experiences. The comprehensive architecture encompasses data collection, processing, and application layers, supported by robust communication protocols and security measures. This integration addresses critical challenges in interoperability, scalability, and reliability while optimizing network performance and power management. The implementation framework incorporates stringent development standards and maintenance procedures, ensuring system sustainability and efficiency. Future considerations include emerging technologies like artificial intelligence, edge computing, and blockchain, alongside scalable infrastructure planning to accommodate evolving healthcare needs.